Taxonomic treatment of the Mesoamerican genus Rovaeanthus (Rondeletieae, Rubiaceae) - Torres-Montúfar, Alejandro; Ochoterena, Helga (Phytotaxa, 2019)
Rovaeanthus (Rondeletieae, Rubiaceae) is a Mesoamerican endemic genus of two species, characterized by a fleshy, pubescent ring at the corolla mouth. Despite the molecular evidence, which suggested that Rovaeanthus shares a most recent common ancestor with the rest of the tribe Rondeletieae, it was treated as a synonym of Rogiera (Guettardeae), with which it shares the pubescent ring at the corolla mouth. Although the species circumscription of Rovaeanthus is clear, its recognition as a separate genus is not yet widely accepted. An updated identification key for the two species of Rovaeanthus, descriptions, distribution maps, phenological data, conservation status, and illustrations are provided.